DOES SPIRITUAL PHILOSOPHY MATTERS ON LOCAL MICROFINANCE IN BALI? - Suryandari, Ni; Widnyana, I Wayan (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
The massive growth of LPDs means that they must have excellent performance. LPDs are not protected by the government, so they must have good financial governance. The existence of LPDs is needed to support traditional villages and be able to synergize with Hindu philosophy in improving LPD performance. This study aims at determining the effect of four Hindu's philosophy on Lembaga Perkreditan Desa (LPD) performance as a local microfinance in Bali. The samples in this study were 64 respondents consisting of 32 chairman and 32 supervisory boards from LPD in Ubud Gianyar. The analytical method used Moderated Regression Analysis. The results showed that Dharma, Artha, Kama, and Moksa have a positive effect on LPD's performance. The better the application of Dharma, artha, kama, and moksa in the organization, the employees will do good things in accordance with applicable norms.